Anaesthesia in Veterinary Oncology: The Effects of Surgery, Volatile and Intravenous Anaesthetics on the Immune System and Tumour Spread - Ana Vidal Pinheiro; Gonçalo N. Petrucci; Amândio Dourado; Isabel Pires (Animals, 2023)
Throughout the course of oncological disease, the majority of patients require surgical, anaesthetic and analgesic intervention. However, during the perioperative period, anaesthetic agents and techniques, surgical tissue trauma, adjuvant drugs for local pain and inflammation and other non-pharmacological factors, such as blood transfusions, hydration, temperature and nutrition, may influence the prognosis of the disease. These factors significantly impact the oncologic patient’s immune response, which is the primary barrier to tumour progress, promoting a window of vulnerability for its dissemination and recurrence. More research is required to ascertain which anaesthetics and techniques have immunoprotective and anti-tumour effects, which will contribute to developing novel anaesthetic strategies in veterinary medicine.